Gen-Z financial keys: the impact of self-control and financial literacy mediated financial behavior - Suprapto, Yandi; Valentina, Sania; Haryanto, Hery (Manajemen dan Bisnis, 2025)
This study investigates the relationship between self-control and financial literacy on the financial well-being of Generation Z, with financial behavior serving as a mediating variable. A quantitative research design was employed, utilizing a convenience sampling technique by distributing questionnaires to Gen-Z individuals residing in Batam. The final sample consisted of 415 respondents, and the data were analyzed using partial least squares structural equation modeling (PLS-SEM). The structural model assessment reveals that both financial literacy and financial behavior exert a significant positive influence on financial well-being, whereas self-control does not exhibit a direct significant impact. Nonetheless, financial behavior effectively mediates the relationship between self-control, financial literacy with financial well-being. These findings highlight the crucial role of enhancing financial literacy and fostering sound financial behavior to improve the financial well-being of the younger generation.